A method for preparing a lithium adsorbent, a composite membrane of the lithium adsorbent, and a method for preparing the same
Patent Information
- Application Number
- CN202511940518.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-22
- Publication Date
- 2026-10-16
AI Technical Summary
文献《EnablinghighlystructurestabilityandadsorptionperformancesofLi1.6Mn1.6O4byAl-gradientsurfacedoping》使用AlCl3·6H2O作为掺杂铝源,但根据文献展示数据,掺杂后的锰系吸附剂在吸附容量上有一定的提升,但锰溶损率依旧在2%以上,难以维持长时间的循环利用
[0018] This invention uses the sol-gel method to dope Al. 3+ It can make the material mix evenly and replace part of the Mn in the material. 3+ The Al-O bond energy is higher than the Mn-O bond energy, which reduces manganese leaching and extends the service life. By adjusting the internal pore size of the composite membrane through PVP, the water flow rate of the composite membrane is increased, allowing the lithium ion sieve inside the membrane to fully contact the adsorbent. This enables rapid and high-capacity selective adsorption of lithium ions in complex salt lake brines with high magnesium-to-lithium ratios and high salinity, while further inhibiting manganese leaching, thereby improving the recycling capacity.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane adsorbent technology, and in particular to a method for preparing a powdered aluminum-doped manganese-based lithium extraction adsorbent, including a composite membrane of lithium adsorbent and its preparation method. Background Technology
[0002] With the severe shortage of traditional fossil fuels and the global energy structure shifting towards cleaner and lower-carbon energy sources, the market demand for lithium resources, as a core material for new energy batteries, is experiencing explosive growth. However, global lithium reserves are limited and unevenly distributed, exacerbating the supply-demand imbalance and becoming a bottleneck restricting the sustainable development of the new energy industry.
[0003] Although my country's salt lake brines are rich in lithium resources, Li is generally deficient. + When the concentration is low and it often coexists with high concentrations of sodium and magnesium ions, conventional separation methods are quite difficult to use. In comparison, adsorption methods, due to their ability to target Li... + Its unique screening properties, green and low-carbon characteristics, and ease of operation have garnered widespread attention. Furthermore, for brines with high magnesium-to-lithium ratios, an "adsorption + membrane" coupling process is employed to shorten the production cycle and improve lithium utilization. However, when coupling the two processes, a compromise operating window that balances the efficiency of both needs to be found, increasing the difficulty of system design and control. Coupled systems are more complex than single adsorption or membrane systems, including adsorbent addition / recovery / regeneration systems and membrane separation systems. This results in larger equipment footprints, more complex control systems, and higher technical requirements for operators. The performance of the adsorbent itself also affects the final lithium recovery rate.
[0004] Spinel-type manganese ion sieves (HMO) are considered one of the most promising adsorbent materials for industrial application due to their high theoretical adsorption capacity and excellent selectivity. However, their practical application is limited by the Mn content during the recycling process. 3+ The Jahn-Teller effect causes lattice distortion, leading to high manganese dissolution rates and severely limiting adsorption capacity and cycling stability, posing a significant challenge to its practical applications. In recent years, researchers have utilized surface modification, ion doping, morphology control, and coatings to improve the adsorption capacity and recyclability of manganese-based ion sieves. Among these strategies, ion doping has proven to be an effective means of adjusting material composition and crystal size. Existing doping methods include Na... + Ca 2+ Mg 2+ K + Fe 3+ These doping methods, to some extent, increase the Li... +The adsorption capacity was [value missing], but it still fell short of the theoretical adsorption capacity, indicating that manganese dissolution loss remained relatively high. (Reference: "Enabling highly structural stability and adsorption performances of Li [value missing]") 1.6 Mn 1.6 The paper "O4byAl-gradientsurfacedoping" uses AlCl3·6H2O as the aluminum doping source. However, according to the data presented in the literature, the manganese-based adsorbent after doping has a certain improvement in adsorption capacity, but the manganese dissolution rate is still above 2%, making it difficult to maintain long-term recycling.
[0005] Xia Kaisheng et al.'s patent CN120459942A discloses a La 3+ Doped lithium manganese oxide lithium-ion sieves, their preparation methods and applications, and their solutions for the degradation of Li-ion compounds by manganese-based adsorbents in high magnesium-to-lithium ratio salt lakes. + The problem of poor adsorption performance is not significantly improved, and the high dissolution rate of manganese during the cycle is still a problem.
[0006] Therefore, it is worthwhile to study how to provide a high-capacity selective manganese-based lithium-ion sieve adsorbent that can improve lithium-ion adsorption capacity while effectively inhibiting manganese leaching and extending the adsorbent's service life. Summary of the Invention
[0007] This invention aims to solve the problems of the prior art and provides a method for preparing a lithium adsorbent, including a composite membrane of lithium adsorbent and its preparation method, the specific solution of which is as follows: A method for preparing a lithium adsorbent includes the following steps: (1) EDTA and MnCO3 were mixed in deionized water in a certain proportion, heated and stirred to form a clear solution, and after standing, filtered, washed and dried, manganese chelate was obtained; (2) The manganese chelate obtained in step (1) is added to the sol formed by aluminum sec-butoxide and ethanol, heated and stirred to form a mixed solution, and after the solvent evaporates and becomes solid, it is calcined at high temperature to obtain Mn2O3-Al; (3) The Mn2O3-Al prepared in step (2) is mixed and ground with LiOH·H2O in a certain proportion and then subjected to hydrothermal reaction. After the reaction is completed, a solid product is obtained. (4) The solid product obtained in step (3) is subjected to a second high-temperature calcination to obtain Al. 3+ Doped lithium-ion sieve precursor LAMO; (5) Take the Al obtained in step (4) 3+ The doped lithium-ion sieve precursor LAMO was subjected to acid desorption and filtration until the filtrate reached neutrality, and then dried to obtain Al. 3+Doped lithium-ion sieve adsorbent HAMO.
[0008] In step (1), heating is performed using a water bath with a temperature of 50-70°C; the mass ratio of EDTA to MnCO3 is 1-1.5.
[0009] In step (2), heating is performed using a water bath with a temperature of 40-70°C. The high-temperature calcination is performed by heating to 600-800°C at a heating rate of 2-5°C / min for 5-8 hours.
[0010] In step (3), the Li / Mn ratio is 0.9~1.3; the hydrothermal reaction temperature is 100~150℃; and the reaction time is 24~48h.
[0011] In step (4), the secondary high-temperature calcination involves heating to 300-600°C at a heating rate of 2-5°C / min and calcining for 3-5 hours.
[0012] In step (5), a pickling solution is used, which is hydrochloric acid with a concentration of 0.1~1M; the pickling time is 8~24h.
[0013] A composite membrane comprising a lithium adsorbent, comprising the following components: Polysulfone 10~20wt% Lithium adsorbent 1~10wt% 1-5 wt% porogen Solvent 70~90wt%.
[0014] A method for preparing a composite membrane including a lithium adsorbent includes the following steps: (1) Dissolving, stirring and degassing: Dissolve polysulfone in an organic solvent, add pore-forming agent and lithium adsorbent and stir until uniform. After stirring, perform degassing. (2) Base film preparation: The degassed casting solution is scraped onto a glass plate with a doctor blade and then immersed in a coagulation bath to complete gel phase separation and form a flat sheet membrane; (3) Interfacial polymerization: The flat sheet membrane is immersed in an aqueous solution containing a large amount of amine monomers for a period of time, and the excess water on the surface is removed by airflow. Then the membrane is immersed in an organic solution containing acyl chloride monomers for a period of time. (4) Post-processing: After the interfacial polymerization is completed, the resulting composite film is taken out and subjected to heat treatment (to promote the complete polymerization reaction and improve the degree of crosslinking), and finally cleaned and stored.
[0015] In step (1), the degree of polymerization of polysulfone is 65,000 to 80,000, preferably 70,000 to 80,000.
[0016] In step (1), the organic solvent is any one of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; the porogen is any one or a mixture of two of polyvinylpyrrolidone and polyethylene glycol, wherein the molecular weight of polyvinylpyrrolidone is 30,000 to 40,000; and the molecular weight of polyethylene glycol is 2×10² to 2×10⁴.
[0017] In step (3), the amine monomer is any one or a mixture of two of piperazine and polyethyleneimine; the molecular weight of polyethyleneimine is 300~1800, preferably 600~1000; the acyl chloride monomer is any one or a mixture of two of trimesoyl chloride (TMC), terephthaloyl chloride (TPC), and isophthaloyl chloride (IPC); and the organic solvent is any one of n-hexane and cyclohexane.
[0018] This invention uses the sol-gel method to dope Al. 3+ It can make the material mix evenly and replace part of the Mn in the material. 3+ The Al-O bond energy is higher than the Mn-O bond energy, which reduces manganese leaching and extends the service life. By adjusting the internal pore size of the composite membrane through PVP, the water flow rate of the composite membrane is increased, allowing the lithium ion sieve inside the membrane to fully contact the adsorbent. This enables rapid and high-capacity selective adsorption of lithium ions in complex salt lake brines with high magnesium-to-lithium ratios and high salinity, while further inhibiting manganese leaching, thereby improving the recycling capacity. Detailed Implementation Example 1
[0019] 10g of MnCO3 was weighed and calcined in a muffle furnace at 800℃ for 5 hours (heating rate 2℃ / min) to obtain Mn2O3. Then, the obtained Mn2O3 was mixed with LiOH·H2O at a Li / Mn ratio of 1.2 and ground into a fine powder. This powder was then poured into a reaction vessel and reacted at 120℃ for 48 hours. After natural cooling, the mixture was filtered to obtain a solid product. This solid product was then calcined at 350℃ (heating rate 3℃ / min) for 4 hours to obtain the precursor LMO-1. The obtained precursor was immersed in 0.5M HCl for 12 hours, then washed and filtered until the filtrate was neutral to obtain the manganese-based lithium ion sieve adsorbent HMO-1. Example 2
[0020] 10g of MnCO3 was weighed and calcined in a muffle furnace at 800℃ for 5 hours (heating rate of 2℃ / min) to obtain Mn2O3. Then, the obtained Mn2O3 was mixed with LiOH·H2O at a Li / Mn ratio of 1.2 and ground into a fine powder. This powder was then poured into a reaction vessel and reacted at 120℃ for 48 hours. After natural cooling, the mixture was filtered to obtain a solid product. This solid product was then calcined at 450℃ (heating rate of 3℃ / min) for 4 hours to obtain the precursor LMO-2. The obtained precursor was immersed in 0.5M HCl for 12 hours, then washed and filtered until the filtrate was neutral to obtain the manganese-based lithium ion sieve adsorbent HMO-2. Example 3
[0021] 10g of MnCO3 was weighed and calcined in a muffle furnace at 800℃ for 5 hours (heating rate 2℃ / min) to obtain Mn2O3. Then, the obtained Mn2O3 was mixed with LiOH·H2O at a Li / Mn ratio of 1.2 and ground into a fine powder. This powder was then poured into a reaction vessel and reacted at 120℃ for 48 hours. After natural cooling, the mixture was filtered to obtain a solid product. This solid product was then calcined at 550℃ (heating rate 3℃ / min) for 4 hours to obtain the precursor LMO-3. The obtained precursor was immersed in 0.5M HCl for 12 hours, then washed and filtered until the filtrate was neutral to obtain the manganese-based lithium ion sieve adsorbent HMO-3. Example 4
[0022] First, EDTA and MnCO3 were reacted at 60°C in a mass ratio of 1.5 and allowed to stand for 48 hours. After washing and filtration, manganese chelates were obtained.
[0023] Then, 0.6 g of aluminum sec-butoxide was dissolved in anhydrous ethanol and stirred at 60 °C to form an aluminum sol. Subsequently, 10 g of manganese chelate was added. After the ethanol evaporated, the mixture was ground and calcined in a muffle furnace at 800 °C for 5 h (heating rate 2 °C / min) to obtain Mn₂O₃-Al. Then, the obtained Mn₂O₃-Al was mixed with LiOH·H₂O at a Li / Mn ratio of 1.2 and poured into a reaction vessel. The mixture was reacted at 120 °C for 48 h, and after natural cooling, it was filtered to obtain a solid product. This solid product was then calcined at 350 °C for 4 h (heating rate 2 °C / min) to obtain the precursor LAMO-1. The obtained precursor was immersed in 0.5 M HCl for 12 h, then washed and filtered until the filtrate was neutral to obtain the manganese-based lithium ion sieve adsorbent HAMO-1. Example 5
[0024] First, EDTA and MnCO3 were reacted at 60°C in a mass ratio of 1.5 and allowed to stand for 48 hours. After washing and filtration, manganese chelates were obtained.
[0025] Then, 0.6 g of aluminum sec-butoxide was dissolved in anhydrous ethanol and stirred at 60 °C to form an aluminum sol. Subsequently, 10 g of manganese chelate was added. After the ethanol evaporated, the mixture was ground and calcined in a muffle furnace at 800 °C for 5 h (heating rate 2 °C / min) to obtain Mn₂O₃-Al. Then, the obtained Mn₂O₃-Al was mixed with LiOH·H₂O at a Li / Mn ratio of 1.2 and poured into a reaction vessel. The mixture was reacted at 120 °C for 48 h, naturally cooled, and filtered to obtain a solid product. This solid product was then calcined at 450 °C for 4 h (heating rate 2 °C / min) to obtain the precursor LAMO-2. The obtained precursor was immersed in 0.5 M HCl for 12 h, then washed and filtered until the filtrate was neutral to obtain the manganese-based lithium ion sieve adsorbent HAMO-2. Example 6
[0026] First, EDTA and MnCO3 were reacted at 60°C in a mass ratio of 1.5 and allowed to stand for 48 hours. After washing and filtration, manganese chelates were obtained.
[0027] Then, 0.6 g of aluminum sec-butoxide was dissolved in anhydrous ethanol and stirred at 60 °C to form an aluminum sol. Subsequently, 10 g of manganese chelate was added. After the ethanol evaporated, the mixture was ground and calcined in a muffle furnace at 800 °C for 5 h (heating rate 2 °C / min) to obtain Mn₂O₃-Al. Then, the obtained Mn₂O₃-Al was mixed with LiOH·H₂O at a Li / Mn ratio of 1.2 and poured into a reaction vessel. The mixture was reacted at 120 °C for 48 h, and after natural cooling, it was filtered to obtain a solid product. This solid product was then calcined at 550 °C for 4 h (heating rate 2 °C / min) to obtain the precursor LAMO-3. The obtained precursor was immersed in 0.5 M HCl for 12 h, then washed and filtered until the filtrate was neutral to obtain the manganese-based lithium ion sieve adsorbent HAMO-3. Example 7
[0028] First, EDTA and MnCO3 were reacted at 60°C in a mass ratio of 1.5 and allowed to stand for 48 hours. After washing and filtration, manganese chelates were obtained.
[0029] Then, 1.2 g of aluminum sec-butoxide was dissolved in anhydrous ethanol and stirred at 60 °C to form an aluminum sol. Subsequently, 10 g of manganese chelate was added. After the ethanol evaporated, the mixture was ground and calcined in a muffle furnace at 800 °C for 5 h (heating rate 2 °C / min) to obtain Mn₂O₃-Al. Then, the obtained Mn₂O₃-Al was mixed with LiOH·H₂O at a Li / Mn ratio of 1.2 and poured into a reaction vessel. The mixture was reacted at 120 °C for 48 h, and after natural cooling, it was filtered to obtain a solid product. This solid product was then calcined at 350 °C for 4 h (heating rate 2 °C / min) to obtain the precursor LAMO-4. The obtained precursor was immersed in 0.5 M HCl for 12 h, then washed and filtered until the filtrate was neutral to obtain the manganese-based lithium ion sieve adsorbent HAMO-4. Example 8
[0030] First, EDTA and MnCO3 were reacted at 60°C in a mass ratio of 1.5 and allowed to stand for 48 hours. After washing and filtration, manganese chelates were obtained.
[0031] Then, 1.2 g of aluminum sec-butoxide was dissolved in anhydrous ethanol and stirred at 60 °C to form an aluminum sol. Subsequently, 10 g of manganese chelate was added. After the ethanol evaporated, the mixture was ground and calcined in a muffle furnace at 800 °C for 5 h (heating rate 2 °C / min) to obtain Mn₂O₃-Al. Then, the obtained Mn₂O₃-Al was mixed with LiOH·H₂O at a Li / Mn ratio of 1.2 and poured into a reaction vessel. The mixture was reacted at 120 °C for 48 h, and after natural cooling, it was filtered to obtain a solid product. This solid product was then calcined at 450 °C for 4 h (heating rate 2 °C / min) to obtain the precursor LAMO-5. The obtained precursor was immersed in 0.5 M HCl for 12 h, then washed and filtered until the filtrate was neutral to obtain the manganese-based lithium ion sieve adsorbent HAMO-5. Example 9
[0032] First, EDTA and MnCO3 were reacted at 60°C in a mass ratio of 1.5 and allowed to stand for 48 hours. After washing and filtration, manganese chelates were obtained.
[0033] Then, 1.2 g of aluminum sec-butoxide was dissolved in anhydrous ethanol and stirred at 60 °C to form an aluminum sol. Subsequently, 10 g of manganese chelate was added. After the ethanol evaporated, the mixture was ground and calcined in a muffle furnace at 800 °C for 5 h (heating rate 2 °C / min) to obtain Mn₂O₃-Al. Then, the obtained Mn₂O₃-Al was mixed with LiOH·H₂O at a Li / Mn ratio of 1.2 and poured into a reaction vessel. The mixture was reacted at 120 °C for 48 h, naturally cooled, and filtered to obtain a solid product. This solid product was then calcined at 550 °C for 4 h (heating rate 2 °C / min) to obtain the precursor LAMO-6. The obtained precursor was immersed in 0.5 M HCl for 12 h, then washed and filtered until the filtrate was neutral to obtain the manganese-based lithium ion sieve adsorbent HAMO-6. Example 10
[0034] 15g of PSF resin with a degree of polymerization of 80,000, 80g of N,N-dimethylacetamide, and 5g of polyvinylpyrrolidone with a molecular weight of 40,000 were uniformly mixed at 60℃, stirred to dissolve, and degassed. The mixture was then coated onto a clean glass plate at 30℃ using a 300μm thick doctor blade. After standing for 10 seconds, the plate was completely immersed in a 40℃ coagulation bath for gel curing for 10–60 seconds. It was then removed and rinsed in pure water at room temperature for at least 12 hours. The base film was then immersed in a 0.8w / v% aqueous solution of polyethyleneimine (PEI) for 10 minutes, then removed and purged with an airflow. Subsequently, the base film was immersed in a 0.1w / v% solution of trimesoyl chloride (TMC) in hexane for 2 minutes. After the reaction was complete, the base film was removed, rinsed with hexane solution, and cured in a 60℃ oven for 15 minutes to obtain the composite film. Example 11
[0035] 15g of PSF resin with a degree of polymerization of 80,000, 80g of N,N-dimethylacetamide, 5g of polyvinylpyrrolidone with a molecular weight of 40,000, and 1g of aluminum-doped manganese-based lithium-ion sieve adsorbent were uniformly mixed at 60℃, stirred to dissolve, and degassed. The mixture was then coated onto a clean glass plate at 30℃ using a 300μm thick doctor blade. After standing for 10 seconds, the plate was completely immersed in a 40℃ coagulation bath for gel curing for 10–60 seconds. It was then removed and rinsed in pure water at room temperature for at least 12 hours. The base membrane was then immersed in a 0.8w / v% aqueous solution of polyethyleneimine (PEI) for 10 minutes, then removed and purged with an airflow. Subsequently, the base membrane was placed in a 0.1w / v% solution of trimesoyl chloride (TMC) in hexane for 2 minutes. After the reaction was complete, the base membrane was removed, rinsed with hexane solution, and cured in a 60℃ oven for 15 minutes to obtain the composite membrane. Example 12
[0036] 15g of PSF resin with a degree of polymerization of 80,000, 80g of N,N-dimethylacetamide, 5g of polyvinylpyrrolidone with a molecular weight of 40,000, and 2g of aluminum-doped manganese-based lithium-ion sieve adsorbent were uniformly mixed at 60℃, stirred to dissolve, and degassed. The mixture was then coated onto a clean glass plate at 30℃ using a 300μm thick doctor blade. After standing for 10 seconds, the plate was completely immersed in a 40℃ coagulation bath for gel curing for 10–60 seconds. It was then removed and rinsed in pure water at room temperature for at least 12 hours. The base membrane was then immersed in a 0.8 w / v% polyethyleneimine (PEI) aqueous solution for 10 minutes, then removed and purged with an airflow. Subsequently, the base membrane was placed in a 0.1 w / v% trimesoyl chloride (TMC) hexane solution for 2 minutes. After the reaction was complete, the base membrane was removed, rinsed with hexane solution, and cured in a 60℃ oven for 15 minutes to obtain the composite membrane. Example 13
[0037] 15g of PSF resin with a degree of polymerization of 80,000, 80g of N,N-dimethylacetamide, 5g of polyvinylpyrrolidone with a molecular weight of 40,000, and 3g of aluminum-doped manganese-based lithium-ion sieve adsorbent were uniformly mixed at 60℃, stirred to dissolve, and degassed. The mixture was then coated onto a clean glass plate at 30℃ using a 300μm thick doctor blade. After standing for 10 seconds, the plate was completely immersed in a 40℃ coagulation bath for gel curing for 10–60 seconds. It was then removed and rinsed in pure water at room temperature for at least 12 hours. The base membrane was then immersed in a 0.8 w / v% piperazine (PIP) aqueous solution for 10 minutes, then removed and purged with an airflow. Subsequently, the base membrane was placed in a 0.1 w / v% trimesoyl chloride (TMC) n-hexane solution for 2 minutes. After the reaction was complete, the base membrane was removed, rinsed with n-hexane solution, and cured in a 60℃ oven for 15 minutes to obtain the composite membrane. Example 14
[0038] 15g of PSF resin with a degree of polymerization of 80,000, 80g of N,N-dimethylacetamide, 5g of polyvinylpyrrolidone with a molecular weight of 40,000, and 4g of aluminum-doped manganese-based lithium-ion sieve adsorbent were uniformly mixed at 60℃, stirred to dissolve, and degassed. The mixture was then coated onto a clean glass plate at 30℃ using a 300μm thick doctor blade. After standing for 10 seconds, the plate was completely immersed in a 40℃ coagulation bath for gel curing for 10–60 seconds. The plate was then removed and rinsed in pure water at room temperature for at least 12 hours. The base membrane was then immersed in a 0.8 w / v% piperazine (PIP) aqueous solution for 10 minutes, then removed and purged with an airflow. Subsequently, the base membrane was immersed in a 0.1 w / v% trimesoyl chloride (TMC) n-hexane solution for 2 minutes. After the reaction was complete, the base membrane was removed, rinsed with n-hexane solution, and cured in a 60℃ oven for 15 minutes to obtain the composite membrane. Example 15
[0039] 15g of PSF resin with a degree of polymerization of 80,000, 80g of N,N-dimethylacetamide, 5g of polyvinylpyrrolidone with a molecular weight of 40,000, and 5g of aluminum-doped manganese lithium-ion sieve adsorbent were uniformly mixed at 60℃, stirred to dissolve, and degassed. The mixture was then coated onto a clean glass plate with a 300μm thick doctor blade at 30℃. After standing for 10 seconds, the plate was completely immersed in a 40℃ coagulation bath for gel curing for 10–60 seconds. It was then removed and rinsed in pure water at room temperature for at least 12 hours. The base membrane was then immersed in a 0.8 w / v% piperazine (PIP) aqueous solution for 10 minutes, then removed and purged with an airflow. Subsequently, the base membrane was placed in a 0.1 w / v% trimesoyl chloride (TMC) hexane solution for 2 minutes. After the reaction was complete, the base membrane was removed, rinsed with hexane solution, and cured in a 60℃ oven for 15 minutes to obtain the composite membrane. Test Example 1 - Adsorption Performance and Manganese Dissolution Rate Test Adsorption and desorption experiments were conducted on the lithium ion sieves prepared in the above examples. 0.1 g of the lithium adsorbent prepared in Examples 1-9 was added to a 300 mg / L LiOH solution, shaken for 24 h, and then samples were taken. After filtration and drying, the solid was washed with 0.5 mol / L HCl for 24 h, and then samples were taken to measure the ion concentration. The results are shown in Table 2.
[0040] As can be seen from the table, aluminum doping can improve the Li-type lithium ion sieve's resistance to Li. + While HAMO-3 exhibits excellent adsorption performance and inhibits manganese dissolution, excessive doping can negatively impact the performance of lithium-ion sieves. Calcination temperature also affects performance; higher temperatures reduce manganese dissolution but decrease adsorption capacity. HAMO-3 demonstrates optimal adsorption performance and low manganese dissolution rate.
[0041] Test Example 2 - Selective adsorption experiment using salt lake brine.
[0042] The composition of the salt lake brine used in the test is shown in the table below:
[0043] The prepared composite membrane was used to separate and adsorb the above 1L salt lake brine, and then desorbed with 0.2mol / L HCl hydrochloric acid to obtain a lithium-rich solution. The results are shown in Table 2.
[0044] As can be seen from Table 3-4, as the content of adsorbent increases, the ion content in the lithium-rich solution is highest when the adsorbent content is 2g. If the adsorbent content is further increased, the adsorbent will not be uniformly dispersed and will agglomerate in the membrane, thereby blocking the membrane structure and affecting its lithium-rich performance.
[0045] Table 1. Formulations and Temperature Conditions for Examples 1-9
[0046] Table 2 Adsorption performance and manganese dissolution rate results of Examples 1-9
[0047] Table 3 Comparison of different adsorbent addition ratios in Examples 10-15
[0048] Table 4. Effect of Examples 10-15 on the lithium enrichment performance of the composite membrane.
[0049] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a lithium adsorbent, characterized in that, Includes the following steps: (1) EDTA and MnCO3 were mixed in deionized water in a certain proportion, and after heating and stirring, a clear solution was obtained, yielding a manganese chelate; (2) The manganese chelate obtained in step (1) is added to the sol formed by aluminum sec-butoxide and ethanol, heated and stirred to form a mixed solution, and after the solvent evaporates and becomes solid, it is calcined at high temperature to obtain Mn2O3-Al; (3) The Mn2O3-Al prepared in step (2) is mixed and ground with LiOH·H2O in a certain proportion and then subjected to hydrothermal reaction. After the reaction is completed, a solid product is obtained. (4) The solid product obtained in step (3) is subjected to a second high-temperature calcination to obtain Al. 3+ Doped lithium-ion sieve precursor LAMO; (5) Take the Al obtained in step (4) 3+ The doped lithium-ion sieve precursor LAMO was subjected to acid desorption and filtration until the filtrate reached neutrality, and then dried to obtain Al. 3+ Doped lithium adsorbent HAMO; In step (1), heating is performed using a water bath with a temperature of 50-70°C; the mass ratio of EDTA to MnCO3 is 1-1.
5.
2. The method for preparing a lithium adsorbent as described in claim 1, characterized in that: In step (2), heating is performed using a water bath with a temperature of 40-70°C. The high-temperature calcination is performed by heating to 600-800°C at a heating rate of 2-5°C / min for 5-8 hours.
3. The method for preparing a lithium adsorbent as described in claim 1, characterized in that: In step (3), the Li / Mn ratio is 0.9~1.3; the hydrothermal reaction temperature is 100~150℃; and the reaction time is 24~48h.
4. The method for preparing a lithium adsorbent as described in claim 1, characterized in that: In step (4), the secondary high-temperature calcination involves heating to 300-600°C at a heating rate of 2-5°C / min and calcining for 3-5 hours.
5. The method for preparing a lithium adsorbent as described in claim 1, characterized in that: In step (5), a pickling solution is used, which is hydrochloric acid with a concentration of 0.1~1M; the pickling time is 8~24h.
6. A composite membrane comprising a lithium adsorbent, characterized in that, It includes the following components: Polysulfone 10~20wt% Lithium adsorbent 1~10wt% 1-5 wt% porogen Solvent 70~90wt%.
7. A method for preparing a composite membrane comprising a lithium adsorbent as described in claim 6, characterized in that, Includes the following steps: (1) Dissolving, stirring and degassing: Dissolve polysulfone in an organic solvent, add pore-forming agent and lithium adsorbent and stir until uniform. After stirring, perform degassing. (2) Base film preparation: The degassed casting solution is scraped onto a glass plate with a doctor blade and then immersed in a coagulation bath to complete gel phase separation and form a flat sheet membrane; (3) Interfacial polymerization: The flat sheet membrane is immersed in an aqueous solution containing a large amount of amine monomers for a period of time, and the excess water on the surface is removed by airflow. Then the membrane is immersed in an organic solution containing acyl chloride monomers for a period of time. (4) Post-processing: After the interface polymerization is completed, the resulting composite film is taken out, heat-treated, and finally cleaned and stored.
8. The method for preparing a composite membrane comprising a lithium adsorbent as described in claim 7, characterized in that: In step (1), the degree of polymerization of polysulfone is between 65,000 and 80,000.
9. The method for preparing a composite membrane comprising a lithium adsorbent as described in claim 7, characterized in that: In step (1), the organic solvent is any one of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; the porogen is any one or a mixture of two of polyvinylpyrrolidone and polyethylene glycol, wherein the molecular weight of polyvinylpyrrolidone is 30,000 to 40,000; and the molecular weight of polyethylene glycol is 2×10² to 2×10⁴.
10. The method for preparing a composite membrane comprising a lithium adsorbent as described in claim 7, characterized in that: In step (3), the amine monomer is any one or a mixture of two of piperazine and polyethyleneimine; the molecular weight of polyethyleneimine is 300~1800; the acyl chloride monomer is any one or a mixture of two of trimesoyl chloride, terephthaloyl chloride, and isophthaloyl chloride; and the organic solvent is any one of n-hexane and cyclohexane.
Citation Information
Patent Citations
La < 3 + >-doped lithium manganese oxide lithium ion sieve as well as preparation method and application thereof
CN120459942A